Risk Factors and Protective Factors in the Family of Origin in the Biographies of Two Adult Rehabilitation Centre Wards – Case Study of Two Women - Jaros, Agnieszka (Przegląd Badań Edukacyjnych (Educational Studies Review), 2019)
The article describes risk factors and protective factors in the family of origin of women who – in their adolescence – were subject to formal control of an institution of a system preventing demoralization of children and adolescents. The theoretical analysis was based on the concept of resilience. The main research problem is presented in the following question: What factors (risk and protective) occur in individual experiences of women – former pupils of social rehabilitation centers? The author used the case study method, and the autobiographical narrative interview technique for data collection. Based on the analysis of the obtained material, risk factors and protective factors inherent in the family environment of narrators were listed, the configuration of these factors was reconstructed, and their protective or risk value from the point of view of the development of demoralisation was estimated. The most important conclusion is that the same factors (death of a parent, supportive connections with extended family members) contituted different value in the life of narrators. From the perspective of all-life experience of the studied women, it can be stated that what constituted a risk factor for one of them, protected the other against further demoralisation. It was also revealed that instrumental parentification was an important protective factor against the development demoralisation. The conclusions confirm the importance of a case-by-case approach in assessing the value of individual factors (protective and risk) and their importance for the development and life quality of individuals. A biographical approach to resilience issues has also been shown to be useful.